La crítica ideológica como risa en «Figuraciones en el mes de marzo» de Emilio Díaz Valcárcel - Sotomayor Parrilla, Eduardo Enrigue (Studia Romanica Posnaniensia, 2003)
The aim of this paper is to prove the underlying relation between laugh and the ideological criticism in the novel "Figuraciones en el mes de marzo" by a Puerto Rican writer, Emilio Díaz Valcárcel. The author explains the way of understanding the key words of laugh and ideological criticism. The attention of a leader should be attracted to three lines in the analysis of the novel of question. With these three aspects together, in the ideological project of the novel is given the deeply innovatory significance for a literary, of the necessity of the national liberation for shaping the common collective destiny in the specific case of Puerto Rico. Discussing two of them - 1) the particularly humoristic-satirical tone which fluctuates between the subtle irony and the effect of laugh, 2) the "collage" organization of the novel, the author comes to the third - showing, the high ideological commitment of the writer with the process of independence of Puerto Rico within the space of the beginning of the seventies, he draws his final conclusions about the profound democratic and critical meaning of humour and laugh as the source of the symbolic liberation.